2003
DOI: 10.1177/1206331203251257
|View full text |Cite
|
Sign up to set email alerts
|

Defamiliarizing the Mundane Roadscape

Abstract: It is a popular and academic notion that routine driving along motorways signifies contemporary alienation through a kind of serial "non-space."The author counters these dystopian assumptions about the character of this everyday pursuit by exploring his own experience of driving along England's M6 motorway, showing how roads are enmeshed within unpredictable, multiple flows of ideas, sensations, other spaces and times, narratives, and socialities. By critiquing notions that autospace is inherently linear and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
73
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 12 publications
(10 reference statements)
0
73
0
1
Order By: Relevance
“…There is a huge gulf between the autobiographical approaches presented by Pearce (2000) and Edensor (2003), and the value of time evaluation by Mackie et al (2003). However, there is much to be learned from individual narratives in deconstructing meanings, assumptions and contradictions surrounding travel time use.…”
Section: Setting An Agenda For Travel Time Use Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a huge gulf between the autobiographical approaches presented by Pearce (2000) and Edensor (2003), and the value of time evaluation by Mackie et al (2003). However, there is much to be learned from individual narratives in deconstructing meanings, assumptions and contradictions surrounding travel time use.…”
Section: Setting An Agenda For Travel Time Use Researchmentioning
confidence: 99%
“…Pearce (2000) and Edensor (2003) expand this discussion of music and travel through autobiographical analysis of driving. For Edensor (2003) choosing "drive-time" music to accompany the drive along the M6 (a motorway in Britain) is contextualised by the tempo of driving (speed, congestion, etc.)…”
Section: Travel Time Use In the Information Agementioning
confidence: 99%
See 1 more Smart Citation
“…In spite of this mundane nature, everyday mobile rituals are creative practices demanding focus and skill . Even though they are permeated by relatively un-reflexive habits, as Edensor (2003) suggests, everyday mobility rituals allow for possibilities to transcend the banal, escape uniformity, and to engage in complex interactions that generate the distribution of affect, the building of shared habits, and the solution of common problems. The ritualization of mundane spatial mobilities therefore does not emerge from its expressive symbolic value, but rather its affective consequentiality.…”
Section: Performing Spatial Mobilitiesmentioning
confidence: 99%
“…Lately, research on mundane spatial mobilities has begun to shed light on the taskscapes of transportation-mediated movement and the skills passengers practice in negotiating these environments (e.g. Bissell, 2009;Edensor, 2003;Holley, Jain, and Lyons, 2008;Jones, 2005;Laurier, 2004;Lofgren, 2008;. These studies have clearly shown how mobilities are hard-wrought intersubjective accomplishments, but much less attention has been dedicated to how spatial mobility acts fail to achieve their aims and how social actors need to adjust or abort plans,…”
mentioning
confidence: 99%